2017
DOI: 10.2147/lra.s125811
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anesthesia for labor and delivery in a patient with May–Hegglin anomaly: a case report

Abstract: We report a case of May–Hegglin anomaly (MHA) in a woman who had a successful labor and delivery under epidural anesthesia. MHA is an inherited thrombocytopenia easily misdiagnosed as idiopathic (immune) thrombocytopenic purpura (ITP). Early and appropriate diagnosis of MHA during pregnancy is essential for optimal maternal and neonatal delivery outcome. Additionally, it can avoid unnecessary diagnostic studies, such as bone marrow aspiration and biopsy, and even harmful therapies with corticosteroids, immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several authors reported various anesthesia management in thrombocytopenic patients, by both general [4], [5], [6], [7], [8] and regional [9] anesthesia. We approached this case by regional anesthesia for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported various anesthesia management in thrombocytopenic patients, by both general [4], [5], [6], [7], [8] and regional [9] anesthesia. We approached this case by regional anesthesia for two reasons.…”
Section: Discussionmentioning
confidence: 99%